Comparison of two adjuvant hormone therapy regimens in patients with high-risk localized prostate cancer after radical prostatectomy: primary results of study CU1005 - Kun Chang; Xiao-Jian Qin; Hai-Liang Zhang; Bo Dai; Yao Zhu; Guo-Hai Shi; Yi-Jun Shen; Yi-Ying Zhu; Ding-Wei Ye (Asian Journal of Andrology, 2016)
The role of adjuvant hormonal therapy and optimized regimens for high-risk localized prostate cancer after radical prostatectomy remains controversial. Herein, the clinical trial CU1005 prospectively evaluated two regimens of maximum androgen blockage  or bicalutamide 150 mg daily as immediate adjuvant therapy for high-risk localized prostate cancer. Overall, 209 consecutive patients were recruited in this study, 107 of whom received 9 months of adjuvant maximum androgen blockage, whereas 102 received 9 months of adjuvant bicalutamide 150 mg. The median postoperative follow-up time was 27.0 months. The primary endpoint was biochemical recurrence. Of the 209 patients, 59 patients developed biochemical recurrence. There was no difference between the two groups with respect to clinical characteristics, including age, pretreatment prostate-specific antigen, Gleason score, surgical margin status, or pathological stages. The maximum androgen blockage group experienced longer biochemical recurrence-free survival (P = 0.004) compared with the bicalutamide 150 mg group. Side-effects in the two groups were similar and could be moderately tolerated in all patients. In conclusion, immediate, 9-month maximum androgen blockage should be considered as an alternative to bicalutamide 150 mg as adjuvant treatment for high-risk localized prostate cancer patients after radical prostatectomy.